Study Literature of ICT toward Mathematics Anxiety for Students (Jurusan Matematika FMIPA UNNES, 2023)
Mathematical anxiety is the emergence of feelings of panic, helplessness, inability to act, and unable to control the mentality that occurs when someone is asked to solve mathematical problems. Mathematical anxiety has an influence on student learning outcomes. Researchers conducted an analysis of the studies that have been done related to the use of ICT-based learning media and students' mathematical anxiety. The purpose of this study was to examine in depth the use of ICT-based mathematics learning media to reduce students' math anxiety in learning mathematics. The method used in this research is literature study. The results of this study are students who use ICT as a medium in learning mathematics have lower levels of anxiety than students who do not use ICT as a medium in learning. Therefore, it can be concluded that the use of ICT-based learning media can help reduce math anxiety experienced by students when learning mathematics so as to increase interest, motivation, and student learning outcomes. The suggestion from this research is that further studies can be carried out regarding the maximum use of ICT-based learning media to overcome students' mathematical anxiety.